PENGARUH RELATED DAN UNRELATED DIVERSIFICATION TERHADAP PROFITABILITAS DAN PERTUMBUHAN PERUSAHAAN (Studi Empiris pada Industri Sektor Barang Konsumsi yang Terdaftar di Bursa Efek Indonesia (BEI) Tahun 2019-2023) - Iqlima Firda Anelya; Etna Nur Afri Yuyetta (Diponegoro Journal of Accounting, 2025)
This study examines the impact of related and unrelated diversification on profitability and firm growth in the consumer goods sector listed on the Indonesia Stock Exchange (IDX) during 2019–2023. Using a quantitative, causal-comparative approach, the study employs the Entropy Index (EI) to measure diversification, Economic Value Added (EVA) as a profitability indicator, and Sales Growth (SG) as a proxy for firm growth. The sample includes 24 firms for EVA analysis and 32 firms for SG, selected through purposive sampling. Data were collected from annual reports and financial statements, then analyzed using multiple linear regression with SPSS version 25. The results show that related diversification has no significant effect on either profitability or growth, while unrelated diversification has a significant negative effect on profitability but no effect on growth. These findings suggest that diversification strategies do not always create economic value or sustainable growth, particularly when not supported by effective managerial execution and strategic alignment. This study contributes to the management accounting literature and offers practical insights for firms in developing more targeted and efficient diversification.